Pedagogic Competence in EFL Teaching: An Analysis of Classroom Practices at Junior High School - Daristin, Pipit Ertika; Nailah Maziyah (Ed-Humanistics : Jurnal Ilmu Pendidikan, 2025)
This study aims to explore the pedagogic competence of an English as a Foreign Language (EFL) teacher in teaching English, focusing on three main aspects: learning activities, classroom communication, and assessment practices. The research was conducted as a qualitative case study in Grade VIII Junior High School, with one English teacher as the subject. Data were collected through classroom observations, interviews, and documentation, then analyzed using descriptive qualitative techniques, including data reduction, display, and interpretation. The findings indicate that the teacher demonstrated strong pedagogic competence by designing engaging, technology-based learning activities that utilized tools such as Quizizz, Kahoot, Canva, and educational videos. The use of Problem-Based Learning (PBL) encouraged students to think critically and work collaboratively. The teacher also maintained positive classroom communication and used varied assessment methods, including formative, summative, authentic, and performance-based evaluations. In conclusion, the teacher’s pedagogic competence reflects a student-centered and technology-integrated approach that effectively supports English learning.